Ядра диференціюнапь поліпоміальних кілець та елементи Казиміра - Бедратюк, Л.П. (Український математичний журнал, 2010)
Предлагается алгоритм вычисления элементов ядра произвольного дифференцирования кольца многочленов, который основан на аналоге известного элемента Казимира конечномерной алгебры Ли. С помощью полученного алгоритма ядра дифференцирования Вейтценбека d(xi)=xi−1,d(x0)=0,i=0,…,n, вычислены в случаях n≤6. We propose an algorithm for the evaluation of elements of the kernel of an arbitrary derivation of a polynomial ring. The algorithm is based on an analog of the well-known Casimir element of a finite-dimensional Lie algebra. By using this algorithm, we compute the kernels of Weitzenböck derivation d(x i ) = x i−1, d(x 0) = 0, i = 0,…, n, for the cases where n ≤ 6.